ANALISIS HUBUNGAN PEMBERITAAN MELALUI MEDIA SOSIAL TERHADAP PERSEPSI MASYARAKAT TENTANG COVID 19 DI WILAYAH KERJA PUSKESMAS MEKAR TAHUN 2020 - Dimas Melianto Saputra Bahtiar; Jumakil Jumakil; Irma Irma (FKM Universitas Halu Oleo, 2021)
Perception is a thought process that a person experiences in understanding information in the surrounding environment. The process can be through the senses of vision, hearing and feeling. The number of news on social media such as facebook, Twitter, Instagram, WhatsApp, etc. that discuss the development of Covid-19 affects the community a lot and has changed the order of human life today as well as the public perception of Covid-19 that makes people worried. The purpose of this study is to discover the relationship of news through social media to the community percept about Covid-19 in the work area of puskesmas mekar. The method used in this study is cross-sectional study approach using the stratified proportional random sampling technique for 370 people. Statistical test using the square chi test. The results of the chi-square statistical tests at a confidence level of 95% (0.05) show that p Value < 0.05, shows that there is a significant relationship between the intensity of social media use and the public perception of Covid-19 in the Work Area of Puskesmas Mekar Kota Kendari in 2020.